2011
DOI: 10.5732/cjc.011.10362
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of nucleophosmin induces S-phase arrest in HepG2 cells

Abstract: Nucleophosmin/B23 (NPM) is a universally expressed nucleolar phosphoprotein that participates in proliferation, apoptosis, ribosome assembly, and centrosome duplication; however, the role of NPM in cell cycle regulation is not well characterized. We investigated the mechanism by which NPM is involved in cell cycle regulation. NPM was knocked down using siRNA in HepG2 hepatoblastoma cells. NPM translocation following actinomycin D (ActD) treatment was investigated using immunofluorescent staining. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Analyzing only anagen VI HFs, quantitative immunohistomorphometry of the proliferation marker Ki-67 showed that, compared to scrambled control HFs, β1 integrin -specific silencing significantly reduced the number of Ki-67 + cells (10% less than scrambled control) in the maximally proliferating hair matrix ( Figure 1C ), and also significantly reduced the number of slow-cycling Ki-67 + cells in the HF bulge ( Figure 1D ). These results were double-checked by measuring EdU incorporation, a cell cycle S-phase specific marker to determine active DNA synthesis [ 46 ]. Counting EdU + cells in defined reference areas in the HF bulb and HF bulge, the same proliferation-inhibitory tendency after β1 integrin silencing could be demonstrated in both HF compartments ( Figure 1E , Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing only anagen VI HFs, quantitative immunohistomorphometry of the proliferation marker Ki-67 showed that, compared to scrambled control HFs, β1 integrin -specific silencing significantly reduced the number of Ki-67 + cells (10% less than scrambled control) in the maximally proliferating hair matrix ( Figure 1C ), and also significantly reduced the number of slow-cycling Ki-67 + cells in the HF bulge ( Figure 1D ). These results were double-checked by measuring EdU incorporation, a cell cycle S-phase specific marker to determine active DNA synthesis [ 46 ]. Counting EdU + cells in defined reference areas in the HF bulb and HF bulge, the same proliferation-inhibitory tendency after β1 integrin silencing could be demonstrated in both HF compartments ( Figure 1E , Figure S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…A more specific method to detect cell proliferation is the quantifying of only S-phase active and DNA-synthesizing cells [ 45 ]. By using 5-ethynyl-2'-deoxyuridine (EdU), a terminal nucleoside analog of thymidine, its incorporation during active DNA synthesis [ 46 ] could be visualized because of its labeling with a stabile fluorescence dye. The whole method was performed following the manufacture’s guidelines (Click-iT® EdU Alexa Fluor® 488 Flow Cytometry Assay Kit, Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis is regulated by two major pathways: The death receptor-induced extrinsic pathway and the mitochondria-apoptosome-mediated intrinsic pathway (19). Bcl-2 family proteins are central in controlling the mitochondrial pathway, and >20 members of this family have been identified, including Bcl-2, which is one of the proteins that suppresses apoptosis (20).…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining For immunofluorescence analysis [28] , 2×10 5 cells were plated into each well of a 6-well plate with coverslips. The cells were incubated with 10 μg/mL Chol:MβCD in the presence or absence of 3 μmol/L ezetimibe for 72 h. After the treatment, the cells were washed with PBS.…”
Section: Quantitation Of Intracellular Cholesterol (Hplc and Enzymaticmentioning
confidence: 99%